IARS2-related disease manifesting as sideroblastic anemia and hypoparathyroidism: A case report - Gong, Yan; Lan, Xiao Ping; Guo, Sheng (Frontiers in Pediatrics, 2023)
Background: IARS2 (EC6.1.5) is a mitochondrial isoleucine-tRNA synthetase. Despite the fact that only fewer than 30 patients have been reported in the literature, mitochondrial disorders caused by pathogenic variants in the IARS2 gene (OMIM: 616007) have a very broad and variable clinical phenotype spectrum. We present a child who has sideroblastic anemia and hypoparathyroidism as a result of a previously unreported mutation in the IARS2 gene. Case Presentation: A 14-year-old girl who had been anemic for 12 years was diagnosed with pure red cell aplasia (hemoglobin 42 g/l, reference range 110-160) at the age of 2. Her anemia was resistant to high-dose intravenous gamma globulin and cyclosporine therapy and required monthly blood transfusions to maintain normal hemoglobin levels. She developed cataracts at the age of 6 and was cured by phacoemulsification. At the age of 8, she visited the endocrine department, because of mental and physical retardation accompanied by repeated convulsions, and the antiepileptic treatment was ineffective. She was diagnosed with hypoparathyroidism. To control the convulsions, she was given calcitriol orally as well as large doses of calcium supplements. Due to severe growth and development delays, delayed sexual development, and hypokinesia at the age of 13.5Y, the parents agreed to a whole-exon gene sequencing test. IARS2 gene compound heterozygous variants c.2450G>A (p.Arg817His) and c.2511del (p.Leu838Phefs*69) were discovered. The girl was then diagnosed with IARS2-related disease and given a cocktail therapy of coenzyme Q10, vitamin B2, L-Carnitine and vitamin E. Although the child's clinical symptoms improved, she still experienced intermittent claudication and hip joint pain. The vitamin B6 was discontinued after three months due to its ineffectiveness in treating anemia. Because the child's ferritin levels remained elevated, she was also prescribed long-term oral deferiprone therapy. Conclusion: Our findings broaden the clinical and genetic spectrum of IARS2-associated disease, and case summaries help raise clinical awareness of IARS2-associated disease and reduce under- and misdiagnosis.